Gastric accumulation of enteral nutrition reduces pressure changes induced by phasic contractility in an isovolumetric intragastric balloon. Issue 7 (3rd February 2021) - Goelen, Nick; Doperé, Glynnis; Byloos, Kris; Ghysels, Stefan; Putzeys, Guido; Vandecaveye, Vincent; Morales, John; Van Huffel, Sabine; Tack, Jan; Janssen, Pieter
Abstract: Background: An isovolumetric intragastric balloon to continuously measure gastric phasic contractility was recently developed by us. We aimed to investigate the readout of this technique in relation to gastric content and gastric emptying. Methods: In this crossover investigation, the VIPUN TM Gastric Monitoring System, which comprises a double lumen nasogastric feeding tube with integrated intragastric balloon, was used to assess phasic gastric contractility by interpretation of the pressure in an isovolumetric balloon in 10 healthy subjects. Balloon pressure was recorded in fasted state, during a 2‐hour intragastric nutrient infusion (1 kcal/ml at 25, 75, or 250 ml/h) and 4 hours post‐infusion, and quantified as Gastric Balloon Motility Index (GBMI), ranging from 0 (no contractility) to 1 (maximal contractility). Gastric accumulation was quantified with magnetic resonance imaging and gastric emptying with a 13 C‐breath test. Results are expressed as mean(SD). Key Results: GBMI was significantly lower during infusion at 250 ml/h compared to baseline (0.13(0.05) versus 0.46(0.12)) and compared to infusion at 25 (0.54(0.21)) and 75 ml/h (0.43(0.20)), all P  < 0.005. Gastric content volume was larger after infusion at 250 versus 75 ml/h ( P  < 0.001). Half‐emptying time and accumulation were both negatively correlated with postprandial contractility. Postprandial GBMI was significantly lower when GCV>0 ml compared to when the stomach was empty. Conclusions and Inferences: Enteral nutrition dose‐dependently decreased the contractility readout. This decrease was linked to gastric accumulation of enteral nutrition.